PERAN PEMBIMBING KEMASYARAKATAN DALAM MENGATASI KECEMASAN ANAK BERHADAPAN DENGAN HUKUM PADA TAHAP PRA-AJUDIKASI: SEBUAH STUDI KUALITATIF - Faradilla, Widya (Politeknik Ilmu Pemasyarakatan, 2025)
Children in conflict with the law (CCL) frequently experience heightened anxiety during the pre-adjudication stage, a period that substantially affects their psychological well-being and their capacity to engage effectively with the legal process. The role of probation officer (Pembimbing Kemasyarakatan/PK) is therefore critical in providing emotional support, safeguarding children’s rights, and assisting them in managing anxiety throughout legal proceedings. This study aims to examine the strategies and approaches employed by PK officers in reducing anxiety among CCL, explore the perceived effectiveness of their interventions from multiple stakeholder perspectives, and identify factors that facilitate children’s ability to cope with pre-adjudication anxiety. A qualitative descriptive design was employed, utilizing in-depth interviews, observation, and document analysis. The study involved seven informants, including two CCL, one parent, one investigator, one public prosecutor, and two PK officers directly handling the cases. Observations were conducted to assess whether PK supervision influenced the children’s emotional responses and stress levels during the pre-adjudication phase. The findings indicate that anxiety among CCL manifests across emotional, psychological, and cognitive dimensions. PK interventions—comprising assessment, guidance, individual counseling, and group counseling—play a substantive role in mitigating these anxiety reactions. Supportive factors include consistent PK involvement, social and environmental support, and family participation, all of which contribute to reducing the child’s anxiety and enhancing their adaptive functioning. Overall, the study demonstrates that PK officers serve an essential function in alleviating anxiety among CCL through intensive supervision that provides both moral support and practical guidance in navigating legal procedures, thereby improving confidence, lowering emotional tension, and strengthening the child’s capacity to cope during pre-adjudication..